PENGARUH KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU: A LITERATURE REVIEW IN INDONESIAN CONTEXT - Indah, Rafika; Hariri, Hasan; Rini, Riswanti; Rusdiani, Atik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
The performance of qualified and professional teachers is one of the key factors for success in school learning. The better the teacher's performance, the better the quality of educational services. There are many factors that influence teacher performance. One of them is the leadership of the school principal. Among the various styles of school principal leadership, this article focuses on analyzing the influence of situational leadership of school principals on teacher performance, which has so far received little attention from researchers. This research uses a literature review method, where data is collected through articles from 2014 to 2023. A total of 14 articles were collected through Google Scholar. The results of the study show that there is a positive and significant influence of situational leadership of school principals on teacher performance. This article is expected to be a reference for further research from a theoretical aspect, namely to increase knowledge about the influence of situational leadership of school principals on teacher performance.